The potential of bilimbi leaf (Averrhoa bilimbi L.) extract as an inhibitor of Staphylococcus epidermidis growth - Asnur, Andi Muhammad Nawwar; Waspodo, Nurelly N; Irwan, Andi Alamanda; Sodiqah, Yani; Mangarengi, Yusriani (Universitas 'Aisyiyah Yogyakarta, 2025)
Coagulase-negative staphylococci (CoNS) are part of the normal skin flora and are often considered to be minimally pathogenic or even non-pathogenic. However, in certain cases, CoNS bacteria can lead to increased morbidity and mortality, particularly in high-risk patients. This study aims to examine the inhibition zones of Staphylococcus epidermidis following treatment with bilimbi (Averrhoa bilimbi L.) leaf extract at concentrations of 50%, 75%, and 100%, and to compare the inhibition zones across these three concentrations. This research employed a laboratory experimental design using the Kirby-Bauer disc diffusion method. The results showed that the inhibition zones for Staphylococcus epidermidis treated with 50% extract concentration were 12.78 mm, 13.01 mm, and 13.10 mm, classified as intermediate. At a 75% concentration, the inhibition zones were 13.07 mm, 13.40 mm, and 15.12 mm, ranging from intermediate to sensitive. Meanwhile, the 100% concentration produced inhibition zones of 15.64 mm, 16.89 mm, and 17.1 mm, classified as sensitive. A comparative analysis of the inhibition zones indicated that the 100% concentration produced the largest zone of inhibition among the three concentrations tested.